The Effect of Work Life Balance on Job Satisfaction with Work Stress as a Mediating Variable "PT. JNE (Nugraha Ekakurir Line) Express Ambon Branch" - Harvey Hiariey; Conchita V. Latupapua; Agusthina Risambessy; Tesalonika Brely Adela Sahalessy (East Asian Journal of Multidisciplinary Research, 2022)
This study discusses how work life balance affects job satisfaction with work stress as a mediating variable (among employees of PT. JNE Express Ambon Branch). The purpose of this study was to examine and analyze the effect of work stress mediating work life balance on job satisfaction. With a total population of 39 and the sampling technique using simple random sampling technique by calculating slovin totaling 35 employees of PT. JNE Express Ambon Branch. The analytical test tool used is Smart PLS 3.0 with the SEM (Structural Equation Modeling) analysis method. The results of this study indicate that work life balance has a significant and significant effect on job satisfaction with a P-Value of 0.000, work life balance has a negative and insignificant effect on work stress with a P-Value of 0.397, work stress has a negative and not significant effect on satisfaction work with a P-Values of 0.543, and finally work stress is not proven to mediate the effect of work life balance on job satisfaction with a P-Values of 0.657.